Stem Cells from Human Exfoliated Deciduous Teeth Attenuate Trigeminal Neuralgia in Rats - Xiaofeng Bai; Xuedi Zhang; Chun Wang; Yao Liu; Xuemei Liu; Yu Fan; Xia Zhang (Stem Cells International)
Trigeminal neuralgia is an incurable progressive nervous system disease that can last for several months or years. Stem cells from human exfoliated deciduous teeth (SHED) are a candidate source for cell-based therapy. Owing to their neuroprotective and immunomodulatory effects, these neural crest cells have potential roles in mediating chronic pain. In this study, we established a rat model of chronic constriction injury of the infraorbital nerve (CCI-ION) to evaluate the analgesic effect of SHED in neuropathic pain. The effects of local SHED transplantation on inflammatory cell infiltration in the trigeminal nerve were investigated based on hematoxylin and eosin staining. The levels of proinflammatory factors in the injured nerve and transient receptor potential vanilloid type 1 (TRPV1) expression in the trigeminal nerve and ganglion were quantified. The data showed that systemic or local injection of SHED attenuated the sensitivity of rats to mechanical stimuli after nerve injury, and this effect lasted throughout the observation period of 8 weeks. PKH26-labeled SHED were distributed to the ipsilateral trigeminal ganglions 24 and 72 hours after local injection. SHED transplantation at the lesion site led to reduced inflammatory cell infiltration and proinflammatory cytokine levels in the injured nerve and inhibited CCI-ION-induced upregulation of TRPV1 expression in the trigeminal nerve and ganglion in the early phase. Therefore, these results provide preclinical evidence that supports the use of SHED in the treatment of trigeminal neuralgia and potentially other chronic pain conditions.